Eco-Friendly Induction of Systemic Resistance against Insect Pests and Diseases in Vegetables Using Neem-Enriched Organics and Inoculation of Beneficial Soil Microbes - Raju Lal Bhardwaj; Anita Sharma; Premlata Meena (Journal of the Indian Society of Soil Science, 2026)
The overuse of agrochemicals, along with intensive irrigation, has led to an escalation in insect pests and disease infestations in vegetable crops, causing significant economic losses and environmental and health hazards. In contrast, neem-added organic manure enriched with plant growth-promoting micro-organisms (PGPMs) has proven to be an effective organic amendment for organic vegetable production, improving soil quality and strengthening plants’ natural defence against insect pests and diseases. A long-term experiment was conducted from 2019-20 to 2023-24 at the College of Agriculture, Sumerpur-Pali, to examine the impact of six different combinations of chemical fertilizers and neem-added organic manures, along with plant growth-promoting microorganisms, on the induction of systemic resistance in various vegetable crops. The results showed that replacing chemical fertilizers by neem-added organic manure, in presence of PGPMs, significantly enhanced the plants’ ability to defend themselves and reduced insect pests and disease damage in comparison to chemical fertilizers across various vegetables by 75.51% in potatoes, 67.40% in onions, 71.81% in radishes, 65.47% in tomatoes, 63.80% in brinjal, and 64.57% in okra. These findings highlight the vital role of neem-added compost and beneficial soil microbes in inducing systemic resistance, reducing the need for agrochemicals, and improving food safety.